Does player unavailability affect football teams` match physical outputs? A two-season study of the UEFA champions league - Windt, J.; Ekstrand, J.; Khan, K. M.; McCall, A.; Zumbo, B. D. (Journal of Science and Medicine in Sport, 2018)
Objectives: Player unavailability negatively affects team performance in elite football. However, whether player unavailability and its concomitant performance decrement is mediated by any changes in teams` match physical outputs is unknown. We examined whether the number of players injured (i.e. unavailable for match selection) was associated with any changes in teams` physical outputs. Design: Prospective cohort study. Methods: Between-team variation was calculated by correlating average team availability with average physical outputs. Within-team variation was quantified using linear mixed modelling, using physical outputs - total distance, sprint count (efforts over 20 km/h), and percent of distance covered at high speeds (>14 km/h) - as outcome variables, and player unavailability as the independent variable of interest. To control for other factors that may influence match physical outputs, stage (group stage/knockout), venue (home/away), score differential, ball possession (%), team ranking (UEFA Club Coefficient), and average team age were all included as covariates. Results: Teams` average player unavailability was positively associated with the average number of sprints they performed in matches across two seasons. Multilevel models similarly demonstrated that having 4 unavailable players was associated with 20.8 more sprints during matches in 2015/2016, and with an estimated 0.60-0.77% increase in the proportion of total distance run above 14 km/h in both seasons. Player unavailability had a possibly positive and likely positive association with total match distances in the two respective seasons. Conclusions: Having more players injured and unavailable for match selection was associated with an increase in teams` match physical outputs.